Characterization of Jamaican Delonix regia and Cassia fistula Seed Extracts - Andrea Goldson Barnaby; Raymond Reid; Vaughn Rattray; Ruth Williams; Marcel Denny (Biochemistry Research International)
Delonix regia and Cassia fistula seed extracts were evaluated for their antioxidant activity, total phenolics, ash, zinc and fatty acid content. Fourier Transform Infrared Spectroscopy (FTIR) was utilized to assess the chemical functionalities present within the seeds. Antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Trolox equivalent antioxidant capacity (TEAC) assays. Total phenolics were determined by the Folin-Ciocalteu assay. Lipid extracts were characterized by nuclear magnetic resonance spectroscopy and gas chromatography/mass spectrometry. Zinc concentration was determined by atomic absorption spectroscopy. Extracts from the seeds of C. fistula had a higher antioxidant activity, free radical scavenging activity, and phenolic content than D. regia. FTIR revealed that the seeds are a rich source of protein with small quantities of fat. C. fistula extracts contained a higher percentage of total fat than D. regia. Palmitic acid was identified as the predominant saturated fatty acid in both extracts. Oleic acid and linoleic acid were identified in smaller quantities. Seed extracts may be considered for use in food and nutraceutical applications.